Long‐term exposure to air pollution and liver cancer incidence in six European cohorts. Issue 11 (14th August 2021) - So, Rina; Chen, Jie; Mehta, Amar J.; Liu, Shuo; Strak, Maciej; Wolf, Kathrin; Hvidtfeldt, Ulla A.; Rodopoulou, Sophia; Stafoggia, Massimo; Klompmaker, Jochem O.; Samoli, Evangelia; Raaschou‐Nielsen, Ole; et al.
Abstract: Particulate matter air pollution and diesel engine exhaust have been classified as carcinogenic for lung cancer, yet few studies have explored associations with liver cancer. We used six European adult cohorts which were recruited between 1985 and 2005, pooled within the "Effects of low‐level air pollution: A study in Europe" (ELAPSE) project, and followed for the incidence of liver cancer until 2011 to 2015. The annual average exposure to nitrogen dioxide (NO2 ), particulate matter with diameter <2.5 μm (PM2.5 ), black carbon (BC), warm‐season ozone (O3 ), and eight elemental components of PM2.5 (copper, iron, zinc, sulfur, nickel, vanadium, silicon, and potassium) were estimated by European‐wide hybrid land‐use regression models at participants' residential addresses. We analyzed the association between air pollution and liver cancer incidence by Cox proportional hazards models adjusting for potential confounders. Of 330 064 cancer‐free adults at baseline, 512 developed liver cancer during a mean follow‐up of 18.1 years. We observed positive linear associations between NO2 (hazard ratio, 95% confidence interval: 1.17, 1.02‐1.35 per 10 μg/m 3 ), PM2.5 (1.12, 0.92‐1.36 per 5 μg/m 3 ), and BC (1.15, 1.00‐1.33 per 0.5 10 −5 /m) and liver cancer incidence. Associations with NO2 and BC persisted in two‐pollutant models with PM2.5 . Most components of PM2.5 were associated with the risk of liver cancer, with the strongest associations for sulfur and vanadium, which were robust to adjustment for PM2.5 or NO2 . Our study suggests that ambient air pollution may increase the risk of liver cancer, even at concentrations below current EU standards. Abstract : What's new? Air pollution contains a number of known carcinogens. While air pollution is classified as carcinogenic and is a known risk factor for lung cancer, the evidence for cancers in other organs is limited. In this large European study, the authors detected associations between air pollution and liver cancer incidence, even at levels that are below current EU standards. These results corroborate findings from several earlier, substantially smaller studies, and suggest that ambient air pollution may increase the risk of liver cancer.